Perceptions of wooden interior product quality : insights on sustainability views among Finnish consumers - Harju, Charlotta; Lähtinen, Katja (Suomen Metsätieteellinen Seura ry, 2021)
Evaluation of product attributes and the overall quality significantly affect consumer purchasing decisions. Previous studies on wooden products have mostly addressed wood product quality from technical viewpoints, while largely disregarding environmental, social, and economic aspects in the assessments. Therefore, knowledge on how sustainability aspects are evaluated as a feature of wood product quality is narrow. This study investigated consumer perceptions of different quality indicators (i.e., quality cues and attributes) of wooden interior products with a special focus on sustainability and value chain phases. In addition, the connections between consumers’ sociodemographic background and their perceptions of the quality features of wooden interior products were evaluated. The material of the study was based on data gathered in 2018 with a postal survey sent to 1000 people living in Finland with a response rate of 25.6%. As methods of analysis, exploratory factor analysis, the Mann-Whitney U test, and the Kruskall-Wallis test were utilized. The results show that the quality indicators of wooden interior products can be grouped into four factors relating to products’ environmental friendliness, fit with lifestyle and home design, visual and tactile attractiveness, and technical solidity, which are in multiple ways connected with sustainability. The sociodemographic background of the respondents was found to be linked with consumer scores for those factors. Engaging consumers in sustainable consumption choices requires providing them with information on wooden product value chains that meets their individual needs in relation to their existing knowledge of those issues and individual values.
Keywords: perceived quality; consumer behavior; sociodemographic variables; sustainable consumption; consumer behaviour; wood products; fi=Markkinointi|en=Marketing|